2016
DOI: 10.1007/s40257-016-0244-y
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Perception in People of Color: A Targeted Educational Intervention

Abstract: Clinicaltrials.gov registration number NCT02437305.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…Melanoma is disproportionally reported among fair-skinned Caucasian populations (6,9,36,37). This variation is partly attributable to decreased photoprotection from reduced melanin (38).…”
Section: Ethnicitymentioning
confidence: 99%
“…Melanoma is disproportionally reported among fair-skinned Caucasian populations (6,9,36,37). This variation is partly attributable to decreased photoprotection from reduced melanin (38).…”
Section: Ethnicitymentioning
confidence: 99%
“…). From 22 included papers, detailed in Table S1 (see Supporting Information), we identified 18 included studies, as three papers reported on the same set of studies, with some reporting additional outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…More intervention studies ( n = 10) engaged in surveillance SSE practices were targeted at those of known risk due to their prior medical history or being older men, compared with focusing on screening SSE practice ( n = 8), for people at no increased risk of skin cancer, including healthy volunteers . Most studies ( n = 11) focused on SSE to detect melanoma, with the remaining ones not differentiating between melanoma and NMSC, but focusing on the detection of skin cancer or not.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations